2007
DOI: 10.1177/1534735407309760
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation, Total Antioxidant Status, and Total Thiol Levels Predict Overall Survival in Patients With Oral Squamous Cell Carcinoma

Abstract: Tobacco is the major etiological factor for oral cancer development through the generation of oxidative stress. Therefore, markers of oxidative stress such as total antioxidant status, lipid peroxidation, and total thiol levels might be useful to monitor oxidative stress and predict overall survival in oral cancer patients. The study included 140 oral cancer patients and 50 healthy controls, who were classified as with the habit of tobacco and no habit of tobacco. Adjacent normal and malignant tissue samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 24 publications
4
38
0
3
Order By: Relevance
“…Tobacco consumption leads to increase in nicotine exposure, and causes heat generation during smoking and pH changes during chewing, affecting bodily fluids such as blood and saliva and resulting in the formation and stabilization of free radicals (23,29). Thus, tobacco consumption causes overproduction of ROS and free radicals that enhance lipid peroxidation levels, and serum and salivary MDA levels are thereby increased, as seen in oral leukoplakia and OSCC patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tobacco consumption leads to increase in nicotine exposure, and causes heat generation during smoking and pH changes during chewing, affecting bodily fluids such as blood and saliva and resulting in the formation and stabilization of free radicals (23,29). Thus, tobacco consumption causes overproduction of ROS and free radicals that enhance lipid peroxidation levels, and serum and salivary MDA levels are thereby increased, as seen in oral leukoplakia and OSCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco consumption causes depletion of thiol (-SH groups) in the redox equation leading to a decrease in buffer activity of antioxidants, and thus tobacco use leads to cancer progression (23). Thus, for predicting the risk of oral carcinogenesis and overall survival of oral cancer patients, lipid peroxidation and thiol levels are useful biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lines of evidence include oxidized DNA found in clinical solid tumor specimens (3,4) and the overexpression of anti-oxidant enzymes in cancer cells (5,6). This higher intrinsic oxidative stress is a result of the overproduction of reactive oxygen species (ROS), potentially through a number of mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with oral cavity cancer exhibited lower total antioxidant capacity, uric acid concentration, salivary peroxidase and superoxide dismutase (SOD) activity in their saliva than did healthy subjects [22,23]. Studies have shown that lipid peroxidation, total antioxidant status, and total thiol levels predict overall survival of oral squamous cell carcinoma patients [24]. Reactive oxygen species (ROS) cause oxidative damage to DNA, protein, and lipids, contributing to mutagenesis and neoplasm formation [25].…”
Section: Introductionmentioning
confidence: 99%